2021
DOI: 10.1016/j.jiph.2021.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, attitudes, and precautionary actions against COVID-19 among medical students in Egypt

Abstract: Background The COVID-19 pandemic has become a significant public health threat. Therefore, the purpose of this survey was to assess knowledge, attitudes, and precautionary measures related to COVID-19 among college students. Methods A convenient sample of 3263 volunteers responded to a self-administered electronic questionnaire during the period from October to December 2020. The knowledge, attitude, and practice (KAP) score level was calculated with a range of 0-34 poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 17 publications
(17 reference statements)
3
14
0
Order By: Relevance
“…Vietnamese students' common sources for seeking information on COVID-19 included social network/ online newspaper (87.61%), mass media (television/ radio) (65.85%), websites of WHO/VMOH, and scientific articles (56.98%), consistent with the results of many other studies conducted in Ecuador (scientific articles: 77.3%) [24], Moroc (social networks: 67.9%) [34], Jordan (social media: 83.4%) [35], Egypt (social media: 75.7%) [36], Ethiopia (television: 83.8%) [18], and Turkey (television: 43%) [37]. Not only Vietnamese students but also students in other countries (Indonesia [13], Bhutan [19], Pakistan [21,26,31], Moroc [34], Jordan [35], and Palestine [38]) had many practical measures which could help to prevent COVID-19, such as avoiding touching eyes/noses/mouths directly, maintaining a distance of at least one meter from others, and avoiding gathering/ going out with friends.…”
Section: Students' Practices Toward Covid-19supporting
confidence: 87%
“…Vietnamese students' common sources for seeking information on COVID-19 included social network/ online newspaper (87.61%), mass media (television/ radio) (65.85%), websites of WHO/VMOH, and scientific articles (56.98%), consistent with the results of many other studies conducted in Ecuador (scientific articles: 77.3%) [24], Moroc (social networks: 67.9%) [34], Jordan (social media: 83.4%) [35], Egypt (social media: 75.7%) [36], Ethiopia (television: 83.8%) [18], and Turkey (television: 43%) [37]. Not only Vietnamese students but also students in other countries (Indonesia [13], Bhutan [19], Pakistan [21,26,31], Moroc [34], Jordan [35], and Palestine [38]) had many practical measures which could help to prevent COVID-19, such as avoiding touching eyes/noses/mouths directly, maintaining a distance of at least one meter from others, and avoiding gathering/ going out with friends.…”
Section: Students' Practices Toward Covid-19supporting
confidence: 87%
“…The continents where most of the research originated were Europe, Asia, and America, with 34.1%, 26.8%, and 24.4% distributions, respectively. Meanwhile, Africa had a lesser distribution, with four studies ( 21 , 29 , 34 , 35 ) (9.8%) included.…”
Section: Resultsmentioning
confidence: 99%
“…A chain-mediation analysis of this phenomenon outlined four essential topics: altruistic motivation, prosocial encouragement, self-moral cognition, and reward ( 42 ). Included studies showed that in terms of gender, female students ( 21 , 24 , 39 , 43 , 44 ) were more likely to be involved in the pandemic control and volunteering than males ( 35 , 40 , 41 ), with a willingness proportion of 60.2% (female) vs. 52.3% (male).…”
Section: Resultsmentioning
confidence: 99%
“…Some KAP surveys have specifically targeted at-risk populations such as health professionals [12]. Others targeted the youth population such as students [13][14][15].…”
Section: Introductionmentioning
confidence: 99%